2015
DOI: 10.1007/s10811-015-0707-1
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific variation in extracellular polysaccharide content and colony formation of Microcystis spp. cultured under different light intensities and temperatures

Abstract: Single cells of five different Microcystis species (M. ichthyoblabe, M. viridis, M. flos-aquae, M. wesenbergii, and M. aeruginosa) were batch-cultured at different temperatures and light intensities: (a) 25°C and 50 μmol photons m −2 s −1 (control culture); (b) 25°C and 10 μmol p h o t o n s m − 2 s − 1 ; a n d ( c ) 1 5°C a n d 5 0 μ m o l photons m −2 s −1 . The extracellular polysaccharide content was significantly higher in treatments b and c than in the control treatment. All Microcystis species existed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…suggested that EPS is an important strategy to reduce Cu 2+ damage because –COO − and some amino groups in EPS can absorb heavy metals effectively48. Xu et al 49. demonstrated that EPS content was significantly lower in M. wesenbergii than the other three Microcystis species under standard culture conditions similar to ours.…”
Section: Discussionsupporting
confidence: 80%
“…suggested that EPS is an important strategy to reduce Cu 2+ damage because –COO − and some amino groups in EPS can absorb heavy metals effectively48. Xu et al 49. demonstrated that EPS content was significantly lower in M. wesenbergii than the other three Microcystis species under standard culture conditions similar to ours.…”
Section: Discussionsupporting
confidence: 80%
“…Xu et al . () induced colony formation from single cells of five Microcystis species at a low temperature of 15°C; their colonies had similar morphologies but differed from most morphologies observed in the field. However, their induced colonies were similar to small unidentified colonies recorded in Lake Taihu (China) during early spring (Fig.…”
Section: Colony Formation In Laboratory Studies and Implications For mentioning
confidence: 91%
“…White arrows point to the visible margin that is filled with mucilage. A–C and E are from Xu et al (), D was provided by Junyi Zhang, and F was provided by Ming Li.…”
Section: Global Success and Morphology Of Microcystismentioning
confidence: 99%
See 2 more Smart Citations